2018
DOI: 10.1021/acs.energyfuels.7b02830
|View full text |Cite
|
Sign up to set email alerts
|

Modeling CH4 Displacement by CO2 in Deformed Coalbeds during Enhanced Coalbed Methane Recovery

Abstract: Gas adsorption and desorption and displacement has a significant effect on coal deformation and permeability evolution during the primary recovery of coalbed methane (CBM) and enhanced coalbed methane recovery (ECBM). The objectives are to (1) quantify the coal deformation and permeability change caused by methane (CH 4 ) displacement with carbon dioxide (CO 2 ) and ( 2) model the transportation of CH 4 and CO 2 in deformed coalbed. In this study, the gas adsorption and desorption and displacement, coal deform… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
23
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 30 publications
(23 citation statements)
references
References 48 publications
0
23
0
Order By: Relevance
“…19 In addition to experimental work, much simulation work has also recently been carried out. Zeng et al 20 used a coupled adsorption-strain model and Transport of Unsaturated Groundwater and Heat Simulator (TOUGH2) to simulate the enhanced coalbed methane recovery process. Their results suggested that it takes about 1800 days to displace 90% of methane considering the coal deformation and permeability change.…”
Section: Introductionmentioning
confidence: 99%
“…19 In addition to experimental work, much simulation work has also recently been carried out. Zeng et al 20 used a coupled adsorption-strain model and Transport of Unsaturated Groundwater and Heat Simulator (TOUGH2) to simulate the enhanced coalbed methane recovery process. Their results suggested that it takes about 1800 days to displace 90% of methane considering the coal deformation and permeability change.…”
Section: Introductionmentioning
confidence: 99%
“…The pore volume obtained by the NLDFT model is slightly lower than the analysis result of the simulation, which might be caused by the effect of ash in the coal matrix. 54 This indicates that the molecular simulation method is accurate for analyzing the pore size distribution of micropores in coal.…”
Section: Resultsmentioning
confidence: 97%
“…Result indicated that super-critical CO 2 on CH 4 recovery was independent of coal rank or maturity, whereas high CO 2 pressure may lead to a negative effect on CH 4 production. Zeng et al 22 proposed an internally-consistent adsorption-strain-permeability model, including gas adsorption/desorption, coal deformation, and permeability evolution, and described the ECBM process of CH 4 displacement by CO 2 . Moreover, Yang et al 23 conducted molecular simulation to reveal the competitive adsorption mechanism of CH 4 , CO 2 , and N 2 in coal.…”
Section: Introductionmentioning
confidence: 99%